2003
DOI: 10.1038/sj.bjc.6600876
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of leucocyte common antigen (LAR) P-subunit in thyroid carcinomas

Abstract: Protein tyrosine phosphatase (PTPase) dephosphorylation and protein tyrosine kinase (PTKs) phosphorylation of key signal transduction proteins may be regulated by extracellular signals, making PTPases important in the regulation of cell proliferation. Leucocyte common antigen (LAR), a receptor-like PTPase, consists of E-subunit, containing the cell adhesion molecule-like receptor region, and P-subunit specific for a short segment of the extracellular region, the transmembrane peptide, and two cytoplasmic PTPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
(42 reference statements)
0
10
1
Order By: Relevance
“…48 -50 In addition, recent reports demonstrated that JNK activation sensitizes cancer cells including urothelial carcinomas to anticancer drug-induced cytotoxicity. 15,37,51 The studies emphasized anti-tumor functions of JNK, which seem to be inconsistent with our present results. There are no critical explanations for this discrepancy, but Igaki and colleagues 52 found that JNK activation switches its proapoptotic effects to survival effects on tumor cells in the presence of oncogenic Ras in Drosophila genetic models.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…48 -50 In addition, recent reports demonstrated that JNK activation sensitizes cancer cells including urothelial carcinomas to anticancer drug-induced cytotoxicity. 15,37,51 The studies emphasized anti-tumor functions of JNK, which seem to be inconsistent with our present results. There are no critical explanations for this discrepancy, but Igaki and colleagues 52 found that JNK activation switches its proapoptotic effects to survival effects on tumor cells in the presence of oncogenic Ras in Drosophila genetic models.…”
Section: Discussioncontrasting
confidence: 57%
“…Statistical analyses were performed using the Fisher's exact test supplemented by the Bonferroni procedures as described previously. 37 Results were considered significant if the P was Ͻ0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, cell lysates were resolved by 10% SDS-PAGE and then transferred to a nitrocellulose membrane (Schleicher & Schuell, Keene, NH). The membrane was blocked with 3% bovine serum albumin in TBS-T [20 mmol/L Tris-HCl (pH 8.0), 137 mmol/L NaCl, and 0.1% Tween 20], incubated with 0.2 Ag/mL anti-PCA-1 antisera at room temperature for 1 hour, and washed thrice with TBS-T. To detect antibody binding, the membrane was exposed to horseradish peroxidase -conjugated anti-rabbit IgG (Santa Cruz Biotech, Santa Cruz, CA) diluted in TBS-T and incubated at room Immunohistochemical analysis of the expression of PCA-1 protein in paraffin-embedded sections of benign prostatic hyperplasia and prostate tumor samples was done as described previously (22). The relative degree of immunostaining was recorded as (À) when <20% of tumor cells were positive, (+) when >20% but <50% of tumor cells were positive, and (++) when over 50% of tumor cells were positive.…”
Section: Methodsmentioning
confidence: 99%
“…Because a cancer stem cell theory has recently been proposed for many malignancies, including PC, we also examined the HNE cases for any association between the presence of stem cells or progenitor cells and NE differentiation using nestin, an intermediate filament protein. The procedure of immunohistochemical staining has been previously described [19] . The antibodies and their conditions are listed in table 2 .…”
Section: F309mentioning
confidence: 99%